TINJAUAN KESIAPAN PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH PROVINSI SULAWESI TENGGARA - Febrilya, Febrilya (JURNAL AKUNTANSI, 2016)
This study aimed to analyze the readiness of Financial Management Board and the Regional Asset (BPKAD) Southeast Sulawesi province in implementing the Government Accounting Standards (SAP) Accrual Based seen from several indicators such Readiness Human Resources and Information Systems. The research is a qualitative research. Data analysis method used is qualitative descriptive analysis method. Data collection techniques in this study were interviews, observation, and documentation.               The results showed that the Financial Management Board and the Regional Asset (BPKAD) Southeast Sulawesi province in implementing the Accrual Based Government Accounting Standards were quite prepared seen from the indicators Readiness Human Resources and Information Systems. This is supported by the technical assistance that has been carried out every year to the employee BPKAD Southeast Sulawesi province in operating SIMDA applications that are now accrual-based. Keywords: Accrual-Based SAP Application Readiness, Human Resources and Information Systems